Ponderal behavior of rats fed an omegas 3, 6 and 9 enriched diet submitted to colon carcinogenesis induced by azoxymethane - Burlamaqui,Idália Maria Brasil (2013)
PURPOSE: To assess weight changes in rats fed diets with different ratios of omegas 3, 6 and 9 submitted to colonic carcinogenesis induced by Azoxymethane (AOM). METHODS: Sixty rats with three weeks of life were distributed into five groups of specific diets containing 12 animals each: GI- Standard diet without adminstration of AOM, GII- Standard diet with adminstration of AOM; GIII- Hyperlipidic diet with adminstration of AOM; GIV-Normolipidic diet with adminstration of AOM; GV- Hypolipidic diet with adminstration of AOM. The weight and food intake of each group were assessed four times in each week throughout the experiment until euthanasia at 36th week. RESULTS: GI and GII had no significant difference in weight. GI showed a significant increase when compared to GIII, GIV and GV. GII also showed a significant increase when compared to GIII, GIV and GV. When comparing intake of GI as compared to GII no significant difference was found, however such groups had higher intake than groups III, IV and V. There were found no difference in weight when comparing amoung rats with and without cancer within each groups: GII, GIII, GIV and GV. CONCLUSIONS: Diets rich in omega 3, 6 and 9 reduced food intake and weight. Rats with colorectal cancer had no decrease in weight as compared to those without this condition in the same group.